A divergent RWP‐RK transcription factor determines mating type in heterothallic Closterium. Issue 5 (9th January 2023) - Sekimoto, Hiroyuki; Komiya, Ayumi; Tsuyuki, Natsumi; Kawai, Junko; Kanda, Naho; Ootsuki, Ryo; Suzuki, Yutaka; Toyoda, Atsushi; Fujiyama, Asao; Kasahara, Masahiro; Abe, Jun; Tsuchikane, Yuki; et al.
Summary: The Closterium peracerosum–strigosum–littorale complex (Closterium, Zygnematophyceae) has an isogamous mating system. Members of the Zygnematophyceae are the closest relatives to extant land plants and are distantly related to chlorophytic models, for which a genetic basis of mating type (MT) determination has been reported. We thus investigated MT determination in Closterium. We sequenced genomes representing the two MTs, mt + and mt −, in Closterium and identified CpMinus1, a gene linked to the mt− phenotype. We analyzed its function using reverse genetics methods. CpMinus1 encodes a divergent RWP‐RK domain‐containing‐like transcription factor and is specifically expressed during gamete differentiation. Introduction of CpMinus1 into an mt + strain was sufficient to convert it to a phenotypically mt− strain, while CpMinus1 ‐knockout mt − strains were phenotypically mt+. We propose that CpMinus1 is the major MT determinant that acts by evoking the mt− phenotype and suppressing the mt+ phenotype in heterothallic Closterium. CpMinus1 likely evolved independently in the Zygnematophyceae lineage, which lost an egg–sperm anisogamous mating system. mt− specific regions possibly constitute an MT locus flanked by common sequences that undergo some recombination.